Gunshot wound of aorta - Quintero, Ariel (Cirugía del Uruguay, 1971)
The author presents the case of a 16-year old girl with a bullet wound in the abdominal aorta, operated under shock with two perfusions of rapid onset. Linen suture was performed and recuperation followed without sequella. This seems to be the first case published in Uruguay of survival of aortic wounds.